Quasiparticle energies and significant exciton effects of monolayered blue arsenic phosphorus conformers. Issue 41 (13th October 2021) - Zhao, Huiyan; Wang, Qian; Jia, Baonan; Han, Lihong; Chen, Wen; Hao, Jinbo; Wu, Liyuan; Lu, Pengfei; Guan, Pengfei
Abstract : The result shows significant anisotropic exciton effects of covering visible regions, which apparently changed the light absorption. The maximum exciton binding energy is up to 0.99 eV. Abstract : Low-dimensional systems have strong multi-body interactions and fewer geometric constraints due to the screening effect of the Coulomb interaction. We use the single-shot GW -Bethe Salpeter equation ( G 0 W 0 -BSE) to calculate the electronic and optical properties of six-blue arsenic phosphorus (β-AsP) conformers. The results show significant anisotropic exciton effects of covering visible regions, which apparently changed the light absorption. The maximum exciton binding energy is up to 0.99 eV, which is more extensive than the black phosphorus monolayer (0.9 eV). We predict that the different orbital contributions to valence bands may cause the anisotropic exciton effect difference. Our results indicate that β-AsP monolayers with the large binding energies of exciton hold a great promise for applications in optoelectronic devices.